2013
DOI: 10.1039/c3ra44465a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous NiO nanoarchitectures for electrochemical energy storage: influence of size, porosity, and morphology

Abstract: The development of flexible, sustainable, and efficient energy storage has recently attracted considerable attention to satisfy the demand for huge energy and power density and meet future societal and environmental needs. Consequently, numerous studies have focused on the design/development of nanomaterials based on mesoporous architectures to improve energy and power densities. We explored how nanoarchitectures in term of morphology, particle size, surface area, and pore size/distribution define energy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…Therefore, several of mesoporous metal oxide nanoparticles have been recently synthesized with controlled compositions, structures, and morphologies due to their composition-, structure-, and morphology-dependent properties and applications [16][17][18]. Among various metal oxides, mesoporous silica nanostructures were extensively studied for their scientific and technological interests including separations, catalysis, sensing, and drug delivery [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several of mesoporous metal oxide nanoparticles have been recently synthesized with controlled compositions, structures, and morphologies due to their composition-, structure-, and morphology-dependent properties and applications [16][17][18]. Among various metal oxides, mesoporous silica nanostructures were extensively studied for their scientific and technological interests including separations, catalysis, sensing, and drug delivery [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was noted that, the copper-ion precursors were effectively controlling the self-assembly of CuO nanoparticles within the hierarchical structures. The induced-water hydrolysis of [Cu(NH 3 ) 4 2 converted to monoclinic CuO due to oxolation process at a relatively higher temperature without a trace of the subsequent annealing treatment in air (eqn (3)). Hence, the copper ions source can modify the subsequent precipitation process, which might affect the competition between thermodynamics and kinetics during the transformation of precursors, nucleation, growth and assembly of CuO nanostructures (see the following equations).…”
Section: Formation Mechanism Of Hierarchical Cuo Micro-/ Nanostructuresmentioning
confidence: 99%
“…However, the actual pseudocapacitance performance of Nickel oxide is still relatively low due to the poor electrical conductivities as well as small specific surface area [18]. It is believed that the morphology and structure play an important role in enhancing the electrochemical performance of NiO [13,16]. Considerable research have demonstrated that nanosized and porous NiO can provide large active surface area for reaction and effective contact between the electrode and electrolyte, which are the key points to enhance the electrochemical performance [19].…”
Section: Introductionmentioning
confidence: 98%
“…As a significant p-type semiconductor, NiO has recently attracted considerable attentions in various application fields [12], such as lithium ion batteries [13], fuel cell electrodes [11], gas sensors [14], catalysts [15] and supercapacitors [16]. Among the investigated supercapacitor materials, NiO has attracted enormous interests owing to its high theoretical capacity (2573 F g À 1 ), low cost and good pseudocapacitive performance [13,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation